STIGMA SOSIAL SUPPORT DENGAN PENGAMBILAN KEPUTUSAN KELUARGA DALAM MELAKUKAN PENGOBATAN PASIEN LANSIA DENGAN GANGGUAN JIWA - Zaky Mubarak; Siti Nafisah (NHM PRESS, 2022)
Mental health is a condition that allows an individual to develop physically, mentally, spiritually and socially so that the individual is aware of his own abilities, can handle pressure, can work productively and is able to make a contribution to his community. The family has a role as the main party that supports the healing process of ODGJ because the family is the party that plays a role in providing care and often interacts with ODGJ. The purpose of this study was to find out the forms of stigma of family social support and decision making regarding treatment for OGDJ and the changes that occur during the healing process. This research uses a qualitative approach with a case study method. Data collection techniques used in this study were non-participant observation, interviews (in-depth interviews) with open questions, and documentation on the research object, namely the patient's family. The results of this study found two themes in the stigma of mental patients, namely the stigma of social support and decisions in decision making.